1993
DOI: 10.1111/j.1464-410x.1993.tb15908.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Balloon Dilatation for Pelviureteric Junction Obstruction

Abstract: A total of 49 retrograde balloon dilatations for pelviureteric junction (PUJ) obstruction were carried out on 43 pelviureteric junctions in 42 patients from 1986 to 1991. The majority (34/43) were performed as primary treatment for PUJ obstruction, with 9 patients having a history of previous open pyeloplasty. Follow-up ranged from 3 months to 4 years (mean 18 months). Clinical improvement, as assessed by absence of symptoms, was seen in 34 cases (80%). There was either no change or an improvement in renograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…The evidence regarding benefit from stent insertion is sparse and contradictory [5]. Double-J stent insertion is commonly performed when balloon disruption of the pelviureteric junction is performed in adults [3], but there are no controlled trials to suggest that stent insertion is necessary for the success of the procedure. Results of animal experiments suggest stenting is not required [9].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence regarding benefit from stent insertion is sparse and contradictory [5]. Double-J stent insertion is commonly performed when balloon disruption of the pelviureteric junction is performed in adults [3], but there are no controlled trials to suggest that stent insertion is necessary for the success of the procedure. Results of animal experiments suggest stenting is not required [9].…”
Section: Discussionmentioning
confidence: 99%
“…The long-term follow-up for the entire group of 33 children averaged 30 months and In all patients a standard dismembered pyeloplasty was performed [10]. A stent (5-Fr feeding tube) was left across the anastomosis and an 8-Fr nephrostomy tube was used to drain the kidney.…”
Section: Methodsmentioning
confidence: 99%
“…spiral CT or endoluminal ultrasonography. Although Hanna et al have provided theoretical support for the Complications concept of endopyelotomy, in that the PUJ (across which they showed the conduction of peristaltic waves) is The only reported complications following the use of this technique are urinoma in one patient [18] and septipreserved [43], it is interesting that Hendren et al have shown that peristalsis across a dismembered PUJ usually caemia (despite antibiotic prophylaxis) in another [19].…”
Section: Balloon Dilatationmentioning
confidence: 99%